Novel Modulatory Effect of L-Type Calcium Channels at Newly Formed Neuromuscular Junctions - Sugiura, Yoshie (J Neurosci, 1997)
This study aimed to examine changes of presynaptic voltage-sensitive calcium channel (VSCC) subtypes during synapse formation and regeneration in relation to transmitter release at the neuromuscular junction (NMJ). Synaptic potentials were recorded from developing rat NMJs and from regenerating mouse and frog NMJs. As in normal adult NMJs, evoked transmitter release was reduced by an N-type VSCC blocker in the frog and by a P/Q-type VSCC blocker in the mammal at immature NMJs; however, various L-type VSCC blockers, both dihydropyridine and nondihydropyridine antagonists,increased evoked but not spontaneous release in a dose-dependent manner at newly formed NMJs. This presynaptic potentiation disappeared as NMJs matured. A rapid intracellular Ca(2+) buffer, bis(O-aminophenoxy)ethane-N,N,N′,N′-tetra-acetic acid-AM, prevented the potentiation effect of nifedipine, but a slow Ca(2+) buffer, EGTA-AM, did not. Thus, the potentiation effect of L-type blockers requires Ca(2+) transients. Pretreatment with Ca(2+)-activated K(+) channel blockers, iberiotoxin or charybdotoxin, did not prevent potentiation by nifedipine at regenerating frog NMJs. Thus, Ca(2+)-activated K(+) channels were not likely involved in this potentiation. In contrast, no additional potentiation by nifedipine was seen in muscles pretreated with pertussis toxin (PTX), a G-protein blocker, which by itself enhances evoked transmitter release at regenerating frog NMJs. These results suggest the existence of multiple subtypes of VSCCs at newly formed motor nerve terminals. In addition to the normal N- or P/Q-type VSCCs that mediate transmitter release, L-type VSCCs may play a novel modulatory role in evoked transmitter release by activating a mechanism linked to PTX-sensitive G-proteins during synapse maturation.